2007
DOI: 10.1146/annurev.psych.56.091103.070145
|View full text |Cite
|
Sign up to set email alerts
|

Moral Emotions and Moral Behavior

Abstract: Moral emotions represent a key element of our human moral apparatus, influencing the link between moral standards and moral behavior. This chapter reviews current theory and research on moral emotions. We first focus on a triad of negatively valenced "self-conscious" emotionsshame, guilt, and embarrassment. As in previous decades, much research remains focused on shame and guilt. We review current thinking on the distinction between shame and guilt, and the relative advantages and disadvantages of these two mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

91
2,336
14
78

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 2,372 publications
(2,613 citation statements)
references
References 164 publications
91
2,336
14
78
Order By: Relevance
“…Social behavior and personal objectives gradually develop around the acquisition of solid and stable moral criteria based on the ability to understand one's own emotions and thoughts as well as those of others (Eisenberg, 2000). Experiences of blame and shame and their good management in the interpersonal domain and play a key role in regulation of social behavior, compliance with regulatory frameworks, and the prevention of violent behaviors (Tangney, Stuewig, & Mashek, 2007) and require empathic processes. Individuals' ability to manage emotional and behavioral responses in harmony with the needs of others and the compromises of being part of a group are necessary to achieve the "moral reciprocity" required for a peaceful coexistence (Ortega, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Social behavior and personal objectives gradually develop around the acquisition of solid and stable moral criteria based on the ability to understand one's own emotions and thoughts as well as those of others (Eisenberg, 2000). Experiences of blame and shame and their good management in the interpersonal domain and play a key role in regulation of social behavior, compliance with regulatory frameworks, and the prevention of violent behaviors (Tangney, Stuewig, & Mashek, 2007) and require empathic processes. Individuals' ability to manage emotional and behavioral responses in harmony with the needs of others and the compromises of being part of a group are necessary to achieve the "moral reciprocity" required for a peaceful coexistence (Ortega, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Moral emotions motivate people to behave in a good way and deter them from immoral behavior (Kroll & Egan, 2004;Tangney, Stuewig, & Mashek, 2007), and research has shown that low levels of moral emotions are associated with school bullying (Menesini & Camodeca, 2008;Menessini et al, 2003;Ttofi & Farrington, 2008). Finally, the high prevalence of c-bullying and c-victimization and the association between c-bullying and MD indicates the need for this form of bullying to be taken into consideration when designing antibullying school intervention programs.…”
Section: Bullying and Cyberbullying 23 23mentioning
confidence: 99%
“…Guilt may even serve as a protective factor against psychopathology in some cases, as it is associated with better anger management (Tangney et al, 1992), later onset of alcohol use (Tangney & Dearing, 2002), and reduced likelihood of drug and alcohol problems (Dearing et al, 2005). These latter findings may be due to guilt-related tendencies to accept responsibility and to repair problems (Tangney et al, 2007).…”
Section: Shame Guilt and Mental Healthmentioning
confidence: 99%
“…Thirdly, despite extremely high rates of psychopathology among adolescent offenders (Teplin et al, 2006) and findings in the adult literature that shame is strongly linked numerous mental health problems (Tangney et al, 2007), no research has yet investigated whether shame is related to psychopathology among youth in the justice system. Thus, we investigated the relationship of guilt and shame with psychopathology among adolescent offenders.…”
Section: The Present Studymentioning
confidence: 99%